2016
DOI: 10.1038/ncomms13206
|View full text |Cite
|
Sign up to set email alerts
|

A direct-sensing galactose chemoreceptor recently evolved in invasive strains of Campylobacter jejuni

Abstract: A rare chemotaxis receptor, Tlp11, has been previously identified in invasive strains of Campylobacter jejuni, the most prevalent cause of bacterial gastroenteritis worldwide. Here we use glycan and small-molecule arrays, as well as surface plasmon resonance, to show that Tlp11 specifically interacts with galactose. Tlp11 is required for the chemotactic response of C. jejuni to galactose, as shown using wild type, allelic inactivation and addition mutants. The inactivated mutant displays reduced virulence in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
56
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 51 publications
2
56
1
Order By: Relevance
“…In this study, we demonstrated that the periplasmic CACHE domain of CqsR QS receptor is involved in signal sensing; and we also identified a common metabolite ethanolamine as a signal that regulates the CqsR QS signaling pathway in V. cholerae . The periplasmic CACHE domain is common in many chemotaxis receptors and other membrane bound regulators (28); and CACHE domain proteins have been shown to interact with a variety of chemical compounds (28, 35, 41, 4648). While CACHE domain has been shown to interact with quaternary ammonium including choline (an ethanolamine analog that CqsR does not interact) to control chemotaxis (49, 50), our study provided an example where a CACHE domain interacts with an amino alcohol (i.e., ethanolamine) to regulate QS gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we demonstrated that the periplasmic CACHE domain of CqsR QS receptor is involved in signal sensing; and we also identified a common metabolite ethanolamine as a signal that regulates the CqsR QS signaling pathway in V. cholerae . The periplasmic CACHE domain is common in many chemotaxis receptors and other membrane bound regulators (28); and CACHE domain proteins have been shown to interact with a variety of chemical compounds (28, 35, 41, 4648). While CACHE domain has been shown to interact with quaternary ammonium including choline (an ethanolamine analog that CqsR does not interact) to control chemotaxis (49, 50), our study provided an example where a CACHE domain interacts with an amino alcohol (i.e., ethanolamine) to regulate QS gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to E. coli and Salmonella , C. jejuni has a more complex chemosensory repertoire and more sophisticated signaling control pathways, which make it an interesting model for signal transduction studies (Lertsethtakarn et al ., ; Day et al ., ). Compared to the 5 chemoreceptors in E. coli and 4 in its close relative Helicobacter pylori , C. jejuni species possess ~10 chemoreceptors, designated as transducer‐like proteins (Tlps) and 2 aerotaxis receptors (Aer1‐2) (Marchant et al ., ; Day et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…A number of C. jejuni chemoreceptors have been shown to have a higher affinity for either CheV or CheW in C. jejuni . The Tlp2, Tlp3 (CcmL), Tlp4 paralogues and Tlp11 (CcrG) chemoreceptor signalling domains have been shown to interact non-preferentially with either CheV or CheW proteins [13-15], whereas the Tlp1 chemoreceptor has demonstrated strong interactions with only the CheV homologue [16].…”
Section: Introductionmentioning
confidence: 99%